Application of seven different clay types in sorbent-modified biodegradability studies with cationic biocides. (April 2020) - Timmer, Niels; Gore, David; Sanders, David; Gouin, Todd; Droge, Steven T.J.
Abstract: The cationic surfactants cetyltrimethylammonium bromide (CTAB) and cetylpyridinium chloride (CPC) can exert inhibitory effects on micro-organisms responsible for their biodegradation. However, under environmentally relevant exposure scenarios the presence of and sorption to organic and inorganic matter can lead to significant reduction of inhibitory effects. In our studies we investigated silica gel and seven clays as inert sorbents to mitigate these inhibitory effects in a 28 day manometric respirometry biodegradation test. CTAB was not inhibitory to the used inoculum, but we did observe that seven out of eight sorbents increased maximum attainable biodegradation, and four out of eight decreased the lag phase. The strongly inhibitory effect of CPC was successfully mitigated by most sorbents, with five out of eight allowing >50% biodegradation within 28 days. Results further indicate that bioaccessibility of the sorbed fractions in the stirred manometric test systems was higher than in calmly shaken headspace test systems. Bioaccessibility might also be limited depending on characteristics of test chemical and sorbent type, with montmorillonite and bentonite apparently providing the lowest level of bioaccessibility with CPC. Clay sorbents can thus be used as environmentally relevant sorbents to mitigate potential inhibitory effects of test chemicals, but factors that impede bioaccessibility should be considered. In addition to apparently increased bioaccessibility due to stirring, the automated manometric respirometry test systems give valuable and highly cost-effective insights into lag phase and biodegradation kinetics; information that is especially relevant for test chemicals of gradual biodegradability. Graphical abstract: Image 1 Highlights: Test chemicals can cause inhibitory effects in standard biodegradation assays. Seven clay sorbents were successfully used to mitigate these inhibitory effects. Bioaccessibility can also be limited by overtly efficient sorbents. Sorbent approach increases the environmental relevance of biodegradation assays. Correct biodegradability assessment improves environmental risk assessment.